2004
DOI: 10.1590/s0104-42302004000400039
|View full text |Cite
|
Sign up to set email alerts
|

Pesquisa em contracepção: opinião de pesquisadores, sujeitos e defensoras dos direitos das mulheres

Abstract: The difficulty experienced by researchers when explaining the meaning of research was surprising. The different opinions about "guinea pig" reflect the controversy about its meaning in research. Certainly the expression "guinea pig" does not apply to all studies however the different meanings identified should make researchers cautious about the ethical issues involved in their studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…They concluded that most of the side effects were slight and well tolerated, that "the percentage of women who said that menstrual cramps, discharge, headaches and irritability had diminished with use of the method was higher than the percentage reporting an increase" and that "the large majority of users (77.2%) rated their experience as 'good' or 'very good'" 31 .…”
Section: The Controversiesmentioning
confidence: 99%
“…They concluded that most of the side effects were slight and well tolerated, that "the percentage of women who said that menstrual cramps, discharge, headaches and irritability had diminished with use of the method was higher than the percentage reporting an increase" and that "the large majority of users (77.2%) rated their experience as 'good' or 'very good'" 31 .…”
Section: The Controversiesmentioning
confidence: 99%